2023
DOI: 10.1002/advs.202207349
|View full text |Cite
|
Sign up to set email alerts
|

YY2‐DRP1 Axis Regulates Mitochondrial Fission and Determines Cancer Stem Cell Asymmetric Division

Abstract: Cancer stem cells (CSCs) are associated with tumor progression, recurrence, and therapeutic resistance. To maintain their pool while promoting tumorigenesis, CSCs divide asymmetrically, producing a CSC and a highly proliferative, more differentiated transit‐amplifying cell. Exhausting the CSC pool has been proposed as an effective antitumor strategy; however, the mechanism underlying CSC division remains poorly understood, thereby largely limiting its clinical application. Here, through cross‐omics analysis, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Recent studies reported that impaired mitochondrial fission resulted in impaired asymmetric division of cancer stem cells (CSC). Downregulation of YY2, the transcription factor of DRP1, was observed in liver CSC in this study …”
Section: Mitochondrial Dynamics In Cancersupporting
confidence: 65%
“…Recent studies reported that impaired mitochondrial fission resulted in impaired asymmetric division of cancer stem cells (CSC). Downregulation of YY2, the transcription factor of DRP1, was observed in liver CSC in this study …”
Section: Mitochondrial Dynamics In Cancersupporting
confidence: 65%
“…YY2 is a zinc‐finger protein and has been reported to have a tumor suppressive function. [ 29 , 30 , 31 , 32 ] A comparative analysis using clinical CRC tissues and corresponding normal adjacent tissues revealed a significant decrease in YY2 mRNA and protein levels in CRC tissues (Figure S3A,B , Supporting Information). Furthermore, YY2 overexpression significantly suppressed the viability and colony‐formation potential of HCT116 cells (Figure S3C,D , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In order to target TFs to regulate the transcription of CSCs and obtain clinical benefits, there are several methods and strategies as follows: (1) TFs gene expression; (6) Inducing ambient pressure such as metabolism, hypoxia and immune response to cause TFs inactivation (Fig. 1).…”
Section: Targeting Tfs or Signaling Pathways In Cscsmentioning
confidence: 99%
“…CSCs occupy a very small amount in tumor tissue, and they have similar TFs and signaling pathways compared to stem cells in healthy tissues [3,4]. One prominent hallmark of CSCs is asymmetric division, which generates more CSCs and specially-differentiated daughter cells [5,6]. Another important feature of CSCs is epithelial-mesenchymal transition (EMT), a reversible cellular process that temporarily puts epithelial cells in a quasi-mesenchymal state.…”
Section: Introductionmentioning
confidence: 99%